Cracking in walls with combined base and end restraint - Micallef,M; Vollum,RL; Izzuddin,BA (Magazine of Concrete Research, 2017)
Restraint of early-age thermal and long-term shrinkage strain can cause cracking in reinforced concrete members. Eurocode 2 provides guidance on the design of crack control reinforcement in reinforced concrete elements with base (edge) and end restraint, but not combined base and end restraint, which commonly occurs. The paper describes an experimental programme, which was conducted to investigate early-age and long-term shrinkage cracking in reinforced concrete walls with combined base and end restraint. The main variables in the test programme were concrete cover and reinforcement ratio. Early-age cracking is simulated with non-linear finite-element analysis, which is shown to capture the observed behaviour adequately. Eurocode 2 gives reasonable estimates of long-term crack widths in the tested walls if edge restraint is assumed, but significantly overestimates crack widths if the worst case of end restraint is assumed.